Perubahan Pola Iklim dan Pengaruhnya terhadap Waktu Panen Duku (Lansium domesticum Corr.) - Sugiarto, Ari; Tanjung, RD; Pratama, R (Seminar Nasional Lahan Suboptimal, 2022)
Sugiarto A, Tanjung RD, Pratama R 2022. Changes in climate patterns and their effects on harvest time of duku (Lansium domesticum Corr.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 859-870. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Climatic factors are essential in the fruit formation and development process of seasonal fruits, such as duku (Lansium domesticum Corr.). This study aimed to determine changes in climate patterns and their relation to the harvest time of duku. This research takes climate study data from 2018 and 2021, the processing and analysis of data to see climate patterns. Observation the harvest time of duku took a case study on plantations located in three villages (Berkat, Kijang Awal Terusan, and Serdang Menang), Sirah Pulau Padang District, Ogan Komering Ilir Regency. The results show that the climate conditions in 2018 and 2021 are not much different, but the climate patterns are very different. The harvest time under climatic conditions in 2018 is in January-February 2019, while the harvest time under climatic conditions in 2021 is in October-November 2021, January 2022, and March 2022. Observation of the harvest time in three villages under climatic conditions in 2018 looks the same, but the harvest time for 2021 climatic conditions is different. The harvest time in Berkat Village is in October and January, Kijang Awal Terusan in January and March, and Serdang Menang in November, January, and March. These results indicate that changes in climate patterns will affect the harvest time of duku.